Towards politically feasible and welfare-improving tax reforms - Felix Bierbrauer; Pierre C. Boyer; Andreas Peichl (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
The design of redistributive tax policies is an evergreen in the public discourse. This column proposes a new approach for the political economy analysis of tax policies based on examining the political support for reforms in contrast to the tax systems themselves. Focusing on monotonic tax reforms, it demonstrates that such reforms are only supported by a majority of the population if the voter with median income is among the beneficiaries. It also yields predictions on how sequences of politically feasible reforms should affect marginal taxes: (1) a shift towards lower marginal tax rates, even negative ones, for below median incomes; (2) pronounced progression for close to median incomes; and (3) a shift to higher and higher marginal tax rates for top earners, unless tax rates in the status quo are already over the top of the Laffer curve.
Keywords: 330